OPTIMALISASI PENERIMAAN RETRIBUSI PADA BALAI PSDA PROGO BOGOWONTO LUK ULO WILAYAH EKS KARISIDENAN KEDU - Andi Widiyanto (Prospect : Jurnal Manajemen dan Akuntansi, 2024)
The background is that there is productive use of land around irrigation by the community which is an asset of the Regional Government, so according to applicable regulations levies/retributions are imposed which will become a source of Regional Original Income. Optimizing income must maintain the sustainability of wealth sources without changing ownership status, the implementation stage is carried out well, efficiently, effectively and sustainably. The aim of the research is to determine the growth rate of levy receipts and determine the effectiveness of levy receipts from 2019 to 2023 at the Progo Bogowonto Luk Ulo PSDA Hall, Kedu Ex-Karisidenan Area. The research method uses quantitative descriptive analysis, data is obtained through observation, documentation and interviews, then the data is analyzed using the Growth Formula and Effectiveness Formula. Research Results (1) The results of the analysis calculations show negative growth in 2020 (-5.49%), positive growth in 2021 (22.12%), positive growth in 2022 (1.91%), positivegrowth in 2023 (9, 56%). (2) The results of effectiveness analysis calculations show that in 2019 (98.61%) the criteria were effective, in 2020 (109.36%) the criteria were very effective, in 2021 (100.06%) the criteria were very effective, in 2022 (100.92%) %) very effective criteria, in 2023 (101.35%) very effective criteria. Conclusion The results of the growth analysis show a dominant positive percentage, the results of the effectiveness analysis show a dominant percentage with very effective criteria, factors that influence optimization include awareness of levy users, levy management services, applicable regulations.